Kebijakan Kredit Usaha Rakyat (KUR) dalam Pandangan "Theory of Justice" John Rawls - Wadyo Pandapotan Pasaribu (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: This article with a title "ThePolicy of People Business Credit (PBC ID: KUR) in the view of John Rawls Theory of Justice" will firstly explain the economic condition of our country (the Republic of Indonesia) from the analysis of experts in economy and governments view to the current economic situation. Next, the discussion is about the formula of the policy of people business credit as an economic policy of Indonesian government in her effort to reduce the number of economic gap or income gap with a business fund allocation to SMEthrough PBC program. Then, this article explains John Rawls general principle of justice which is related to pareto optimalitywhereas on its practical level it is distributive justice that takes effect, in which each actor will get in accordance with his contribution in the market.Â KEYWORDS:people business credit, distributive justice, John Rawls